Illicit Drugs and the Americas: Avoiding a Pax Mafiosa - Tokatlian, Juan Gabriel (Tufts Archival Research Center, 2005)
Volume 31, Issue 2. Summer U.S. national and international drug control strategies over the last four administrations have been largely unsuccessful and have produced substantial negative consequences, such as the unintended empowerment of organized crime in the United States and transnational criminal organizations. To combat the trend, new approaches to the "war on drugs" are needed. This includes a new consensus on controlling illicit drugs.